Probing the local structure of nanoscale actinide oxides: a comparison between PuO2 and ThO2 nanoparticles rules out PuO2+x hypothesis. Issue 1 (6th January 2020) - Bonato, Laura; Virot, Matthieu; Dumas, Thomas; Mesbah, Adel; Dalodière, Elodie; Dieste Blanco, Oliver; Wiss, Thierry; Le Goff, Xavier; Odorico, Michael; Prieur, Damien; Rossberg, André; Venault, Laurent; et al.
Abstract : XRD, EXAFS and HR-TEM study reveals a strong correlation between AnO2 (An = Th and Pu) nanoparticle size and An(iv ) local structure. Abstract : Actinide research at the nanoscale is gaining fundamental interest due to environmental and industrial issues. The knowledge of the local structure and speciation of actinide nanoparticles, which possibly exhibit specific physico-chemical properties in comparison to bulk materials, would help in a better and reliable description of their behaviour and reactivity. Herein, the synthesis and relevant characterization of PuO2 and ThO2 nanoparticles displayed as dispersed colloids, nanopowders, or nanostructured oxide powders allow to establish a clear relationship between the size of the nanocrystals constituting these oxides and their corresponding An(iv ) local structure investigated by EXAFS spectroscopy. Particularly, the first oxygen shell of the probed An(iv ) evidences an analogous behaviour for both Pu and Th oxides. This observation suggests that the often observed and controversial splitting of the Pu–O shell on the Fourier transformed EXAFS signal of the PuO2 samples is attributed to a local structural disorder driven by a nanoparticle surface effect rather than to the presence of PuO2+ x species.